2006
DOI: 10.1128/jb.188.2.499-506.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stringent and Relaxed Recognition of oriT by Related Systems for Plasmid Mobilization: Implications for Horizontal Gene Transfer

Abstract: The plasmids R1162 and pSC101 have origins of conjugative transfer (oriTs) and corresponding relaxases that are closely related. The oriTs are made up of a highly conserved core, where DNA is cleaved by the relaxase prior to transfer, and an inverted repeat that differs in size and sequence. We show that in each case the seven base pairs adjacent to the core and within one arm of the inverted repeat are sufficient to determine specificity. Within this DNA there are three AT base pairs located 4 bp from the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…We previously showed that one of these sites (bp 1306755 to 1306773, Fig. 2) is active for the initiation of plasmid DNA transfer (21). This DNA is between the genes hupB (HU protein ␤ subunit) and ppiD (peptidyl-prolyl cis-trans isomerase) and is unlikely to be part of an integrated plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that one of these sites (bp 1306755 to 1306773, Fig. 2) is active for the initiation of plasmid DNA transfer (21). This DNA is between the genes hupB (HU protein ␤ subunit) and ppiD (peptidyl-prolyl cis-trans isomerase) and is unlikely to be part of an integrated plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…2). The activity of the origin (the proportion of white transconjugant colonies; see Materials and Methods) was 0.75%, indicating that this origin is ϳ15 times more active than the one in Erwinia (21).…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations